Detection of protozoal Trichomonas vaginalis and abnormal vaginal flora in high vaginal smear - Sheela, Wills G.; Vijayalakshmi, P.; Mohanambal, .; Dharishini, Deepa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vagina is the fibro muscular membrane sheath communicating with the uterine cavity and to the exterior at the vulva. Infection of female genital tract results from vaginal flora, extraneous agents and sexually transmitted diseases. The objective of the study was: a) high vaginal smear screening to find out incidence of abnormal vaginal flora of micro-organisms, b) prevalence of protozoal Trichomonas vaginalis. Methods: Rural women from in and around Ammapettai in the age group of 20-50 years attending Gynaecology OPD of SSSMC&RI for vaginal discharge and itching vulva. Exclusion criteria were age less than 20 and above 50 and pruritis vulva due to other causes the study size comprised of 50 women. After getting Institutional ethical committee’s approval and written informed consent from the patients, detailed history regarding type of discharge, odour, itching, and associated bleeding was taken. Per speculum and per vaginal examination done. High vaginal smear for aerobic bacterial profile and Trichomonas infection were taken and transported to microbiology laboratory for staining and culture. Wet mount microscopic examination of Trichomonas vaginalis and Candidiasis with saline and KOH mount done. Results: Out of 100 smears 9 were normal vaginal flora organisms, aerobic pathogens 43%, Trichomonas vaginalis (TV) 30%, and Candida albicans 5% mixed infections on 7 smears. E. coli was seen in 23 samples, Klebsiella in 14, Pseudomonas aeroginosa 4, Staphylococcus in 6 samples. Gram negative organisms were 100% sensitive to imipenem, amikacin and gentamycin and 100% resistant to cefazolin, 80% to ceftazidime, 74% to cefotaxime. Gram positive staphylococcus 50% were resistant to gentamycin, ampicillin. Conclusions: This study reflects on our responsibility to create awareness among women regarding abnormal vaginal discharge through proper health education routine screening targeted treatment to envisage healthy quality life.